Application of Raw and Modified Pomegranate Peel for Wastewater Treatment: A Literature Overview and Analysis - Samia Ben-Ali (International Journal of Chemical Engineering)
The use of renewable substrates as biosorbents has a great attention in wastewater treatment. The pomegranate peel (PGP) constitutes one of these substrates. A review is carried out to investigate the potential of pomegranate peel (PGP) for wastewater treatment. Physical and chemical PGP properties are presented and compared to those of Tunisian pomegranate peel (El Gabsi). Raw and modified PGP performance and sorption capacity for metals, dyes, and organic pollutants are evaluated. Different experimental sorption conditions such as concentration, contact time, pH, temperature, and adsorbent dose used in the literature are illustrated. Studied and best-fitted kinetics and isotherm models to experimental data and thermodynamic parameters are compared. The effects of activating physical and/or chemical conditions on the activated PGP properties are presented. This paper reveals noteworthiness properties of raw PGP for wastewater treatment compared to this activated form. The comparison between activated and raw PGP morphology exhibits that the activation does not necessarily improve the PGP adsorption capacity. Despite a limited research carried out on the raw PGP biosorbent, it appears from this study that it has very good adsorption properties, making it a serious and low-cost renewable substrate toward practical applications in wastewater treatment compared to various other waste agricultural biomass.